Multisensory Stimulation in Rehabilitation of Dementia: A Systematic Review - Andrea Calderone; Angela Marra; Rosaria De Luca; Desirèe Latella; Francesco Corallo; Angelo Quartarone; Francesco Tomaiuolo; Rocco Salvatore Calabrò (Biomedicines)
Background/Objectives: Dementia leads to cognitive decline, affecting memory, reasoning, and daily activities, often requiring full-time care. Multisensory stimulation (MSS), combined with cognitive tasks, can slow this decline, improving mood, communication, and overall quality of life. This systematic review aims to explore methods that utilize MSS in the rehabilitation of patients with dementia. Its clinical value is rooted in its ability to offer a deep comprehension of how MSS can be successfully incorporated into rehabilitation treatments. Methods: Studies were identified from an online search of PubMed, EBSCOhost, Cochrane Library, Web of Science, Embase, and Scopus databases with a search time frame from 2014 to 2024. This review has been registered on Open OSF (n) 3KUQX. Results: Pilot studies investigating MSS interventions, encompassing Cognitive Stimulation Therapy (CST), Sonas therapy, and combined physical–cognitive exercise programs, have yielded mixed findings in individuals with dementia. CST has demonstrated significant improvements in general cognitive function, particularly in language skills, offering a promising approach for cognitive enhancement. Sonas therapy, while showing positive trends in some studies, does not consistently achieve statistically significant outcomes across all cognitive domains. Conversely, combined exercise programs have shown efficacy in improving dual-task performance, suggesting benefits for motor–cognitive integration. MSS delivered within specialized environments like Snoezelen rooms consistently produces positive effects on mood, reducing agitation and promoting relaxation. Conclusions: This review emphasizes how MSS can enhance cognitive, emotional, and behavioral results for individuals with dementia. It is essential for future research to standardize protocols, incorporate advanced technologies such as virtual reality, and rectify diversity gaps. Collaboration between different fields will improve the effectiveness and usefulness of MSS in caring for individuals with dementia.